Effect of gender on auditory brainstem response latencies and thresholds to air-and bone-conducted clicks in newborn infants - Stuart, Andrew; Yang, Edward Y. (East Carolina University, 2001)
Objective: An examination of gender differences in auditory brainstem response (ABR) wave V latencies and thresholds to air-and bone- conducted clicks was undertaken with newborn infants. Design: Two hundred and two full-term newborn infants served as participants (i.e., 103 males and 99 females). Wave V latency measures for air-and bone-conducted click stimuli of 30, 45, and 60 dB nHL and 15 and 30 dB nHL, respectively and thresholds to air-and bone-conducted clicks were determined. Results: Female newborns displayed statistically significant shorter wave V latencies than male newborns for air-conducted click stimuli (p = .0016). There were no significant differences in wave V latencies to bone- conducted click stimuli (p = .11). Females displayed lower ABR thresholds to both air-and bone-conducted stimuli but the differences did not attain statistical significance (p = .054 and p = .18 for air-and bone-conducted stimuli, respectively). Conclusion: The findings of gender disparities in ABR latencies and thresholds to air-conducted clicks may be attributed to either anatomical differences at the periphery or more efficient neural conduction in the auditory nerve and/or brainstem. It was speculated that gender-related Effect of Gender On ABR Latencies and Thresholds 4 differences in bone density or maturation of the skull sutures could affect bone-conducted signal transmission to the cochlea thereby offsetting some inefficiency offered by air-conduction with newborn males. This in turn would minimize gender differences with bone-conducted stimuli.
Effect of Gender on ARB Latencies Thresholds
Keywords: Auditory brainstem response; Latency; Threshold; Gender; Auditory adaptation; Brain stem; Sex differences; Evoked Potentials; Gender identity; Auditory; Brain Stem